Analysis on stress and micromotion on various PEG fixation at glenoid implant - Wahab, A. H. A. (2016)
Six commercially available implant designs were simulated via finite element analysis. The objectives of this study are (1) to determine the effect of peg numbers and orientations to the stress distribution at the implant and cement (2) to compare the micromotion between fully cemented and partially cemented implant. An applied load of 750 N was subjected to the implant at inferior location in which pegs were distributed. The result showed, by increasing the peg numbers, implant stress decreased and increased maximum stress at cement. While, fully cemented implant had higher micromotion compared to partially cemented implant. There are no significant differences between four-fins and six-fins implants under both load conditions. In conclusion, increase in peg numbers results in decreased stress at implant and partially cemented implant can provide better stability in terms of micromotion than fully cemented as it allows bone in-growth between fins. While, adding more fins in partially cemented implant does not influence the micromotion of the implant at all.